Implementation of Service Quality at The Best Resort in Europe, Adare Manor - Rabbani, Rahmi; Gusnadi, Dendi (eProceedings of Applied Science, 2025)
Abstract — The tourism and hospitality industry is a vital and dynamic sector, fueling economic growth, creating jobs, and fostering cultural exchange. With rising globalization and competition, service quality has become the cornerstone of success, especially for luxury resorts, as travelers now seek personalized and memorable experiences. This study focuses on Adare Manor, a leading European resort known for its luxurious offerings and exceptional guest experiences. It examines how the resort achieves outstanding service quality by strategically being ahead than the other resorts in Ireland and a robust guest feedback system. The research also explores how Adare Manor skillfully balances its rich, traditional identity with modern demands to maintain its unique charm and relevance. The findings of this study offer practical insights for other resorts, providing recommendations on how to enhance service standards and ensure long-term competitiveness. Ultimately, this research highlights that superior service quality is not just a competitive advantage it's the fundamental basis for maintaining success in the global hospitality market. Keywords — Resort, Service, Quality